1991
DOI: 10.1080/02646839108403256
|View full text |Cite
|
Sign up to set email alerts
|

Confinement in nulliparous women in the Netherlands: Subjective experiences related to actual events and to post-partum well-being

Abstract: Subjective delivery experiences, obstetrical outcomes and post-partum well-being were studied in 170 nulliparous women who participated in a prospective study on the transition to parenthood. All of the women initially received antenatal care by midwives. Women who gave birth at home and those who gave birth in hospital voluntarily without referral did not differ either with regard to objective outcomes or subjective delivery experiences. Negative experiences were related to referrals during labour; other subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…This is in line with a study that found a significantly negative association between referral and the birth experience 10 days postpartum (Kleiverda et al, 1991). Another study found referral as a significant risk factor for a negative recall of birth experience in women 3 years postpartum (Rijnders et al, 2008).…”
Section: Interpreting the Resultssupporting
confidence: 79%
“…This is in line with a study that found a significantly negative association between referral and the birth experience 10 days postpartum (Kleiverda et al, 1991). Another study found referral as a significant risk factor for a negative recall of birth experience in women 3 years postpartum (Rijnders et al, 2008).…”
Section: Interpreting the Resultssupporting
confidence: 79%
“…Referral during labour has been shown to lead to more negative perceptions of birth experiences in the short and long term compared to not being referred 39–42 . Further research is required to address women’s expectations and attitudes towards birth, birthplace and caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…Referral during labour has been shown to lead to more negative perceptions of birth experiences in the short and long term compared to not being referred. [39][40][41][42] Further research is required to address women's expectations and attitudes towards birth, birthplace and caregiver. Furthermore, it has to be explored whether the antenatal criteria for the assessment 'low risk at start labour' can be improved, to decrease the referral rate during delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluative studies have shown that referral during home delivery does not adversely affect women's perception of the birth process and that 72% of women would again opt for home delivery in a subsequent birth. 18,49,50 It is nevertheless important that women (and, given their high referral rate, nulliparous women in particular) should be informed that risk selection continues up to and during the puerperium, with the ensuing probability of referral even during labour.…”
Section: Discussionmentioning
confidence: 99%
“…18,49,50 It is nevertheless important that women (and, given their high referral rate, nulliparous women in particular) should be informed that risk selection continues up to and during the puerperium, with the ensuing probability of referral even during labour.…”
Section: Discussionmentioning
confidence: 99%